Application of The Tikrar Method in Improving Daily Memory of Prayers in Early Children at Tadika Tahfiz Nur Furqon Lunas Kedah Malaysia - Septiani, Adilah Rizki; Harfiani, Rizka (Pusat Penerbitan Universitas (P2U) Unisba, 2024)
This research aims to determine the increase in students' memorization of daily prayers through the Tikrar method. This research is qualitative research with a field research type using a descriptive approach. Data collection techniques in this research used observation, documentation, and interviews. The data analysis used uses the Miles and Huberman model, namely collecting data, condensing data, presenting data, and drawing conclusions. To test the validity of the data, triangulation techniques were used. The results of this research show that Tadika Tahfiz Nur Furqon applies various strategies for teaching daily prayer, such as reading prayers when starting and ending activities, joint murajaʻah sessions, and assessment schedules. The repetition method (tikrar) is also applied by combining various media according to the child's interests. An assessment system adjusted to the student's age allows for accurate assessment, and the results of the memorization test show that the majority of students succeeded in achieving the memorization target with 77% according to their age. The conclusion from the results of this research positively supports the tikrar method in increasing children's memorization of daily prayers and encouraging the practice of prayer in everyday life.